Effect of Organic and Bio-fertilizer on some yield and quantity parameters for two strawberry varieties Fragaria× ananassa Duch - Salman, Fouad Abass; Jaber, Ayad Jasim (Journal of Kerbala for Agricultural Sciences, 2018)
The study was conducted in Horticulture and Forest Unit at Al-Najaf Agriculture directorate during 2016-2017 growing season, to study the effect of adding some Bio and Organic fertilizer on yield and some quality parameters of strawberry (Fragaria x ananassa Duch) cultivated in plastic house. The first factor included two varieties of strawberry: Albion and Burtela while the second factor was adding seven treatments of organic and bio-fertilizer including: without adding fertilizer (control), adding Azotobecter chroococcum (10g.plant-1), adding of Bacillus subitls (10 ml. plant-1), spraying of organic fertilizer Appetizer (1 ml. plant -1), adding of A.chroococcum + B. subitls, adding A.chroococcum + spraying of Appetizer, adding B. subitls + spraying of Appetizer and adding of A.chroococcum + B. subitls with spraying of Appetizer. Factorial experiment using Randomized Complete Block Design ( R. C. B. D) with three replicates were used.The Duncans multiples range test at 0.05 probabilities was adopted to compare the treatments means. The Bortila variety was significantly increased the fruits number to 27.08 fruit. Plant -1, weight fruit rated to 25.05gm.fruit-1 and yield to 675.50 gm. Plant-1.The type of fertilizer showed a significant increase with adding A.chroococcum + B. subitls + Appetizer sprayed fruit number to 30.00 fruit.plant-1, and fruit weight rated 27.97gm.fruit-1 The Albion variety markedly increased total sugar to 10.54 mg.100gm fresh weight-1, while the Burtela variety showed significantly increase total acidity to 4.29mg.100g fresh weight-1and ascorbic acid to 33.73 mg.100gm fresh weight-1. The fertilizer of A.chroococcum + B. subitls + Appetizer sprayed significantly increased total sugar to 12.11 mg.100gm fresh weight-1, while nitrate content reduces to 14.13mg.100gm dry weight-1. The treatment of A.chroococcum + Appetizer sprayed significantly increased Ascorbic acid to 55.47 mg.100gm fresh weight-1. The control treatment showed significant increase in total acidity 5.35 gm.100gm fresh weight-1 and nitrate content to 19.45 mg.100gm dry weights-1.